Beyond recognition: Women’s rights in unrecognized state-like entities and the role of international law – the case of Transnistria - Cwicinskaja, Natalia (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
Women’s rights cannot be suspended due to the uncertain status of a territory. This study examines how they can be protected in unrecognized entities, with Transnistria as a case study. The aim is to identify the mechanisms – legal, institutional, and societal – through which gender equality and protection from gender-based violence may be advanced despite the absence of international recognition. The study employs a qualitative methodology combining legal doctrinal analysis, case study research, policy analysis and the Human Rights-Based Approach (HRBA), drawing on reports, secondary sources, and expert interviews. The findings show that although constitutional guarantees exist, systemic barriers persist, and the lack of a dedicated genderequality framework leaves women dependent on civil society initiatives and international engagement. The paper concludes that coordinated action – linking legal reform, cross-border cooperation and sustained support for local advocacy – is essential for strengthening women’s rights in Transnistria and other unrecognized entities.